2019
DOI: 10.1007/s11548-019-01965-7
|View full text |Cite
|
Sign up to set email alerts
|

Learning soft tissue behavior of organs for surgical navigation with convolutional neural networks

Abstract: Purpose: In surgical navigation, pre-operative organ models are presented to surgeons during the intervention to help them in efficiently finding their target. In the case of soft tissue, these models need to be deformed and adapted to the current situation by using intra-operative sensor data. A promising method to realize this are real-time capable biomechanical models.Methods: We train a fully convolutional neural network to estimate a displacement field of all points inside an organ when given only the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…We speculate that this also depends on the deformation and its extent, and possibly the organ of interest. Previous work that employs a different spatial discretization, particularly a voxel representation, has found that a target surface of 20% of the visible organ surface was necessary and corresponded to the largest drop in error [ 15 ]. Indeed, this corresponds to the size of the unfiltered stitched surface (Endo) used in [ 23 ] and is roughly half the amount of accessible liver surface that is accessible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We speculate that this also depends on the deformation and its extent, and possibly the organ of interest. Previous work that employs a different spatial discretization, particularly a voxel representation, has found that a target surface of 20% of the visible organ surface was necessary and corresponded to the largest drop in error [ 15 ]. Indeed, this corresponds to the size of the unfiltered stitched surface (Endo) used in [ 23 ] and is roughly half the amount of accessible liver surface that is accessible.…”
Section: Discussionmentioning
confidence: 99%
“…However, the liver may deform under pressure exerted by surgical instruments, characterizing soft tissue deformation. Characteristic hepatic tissue deformations occur either in the first operative steps (upon mobilization of the liver or transection of the liver parenchyma), or during laparoscopy by abnormally high pressure of the capnoperitoneum (12)(13)(14)(15). The grade of deformation depends on the liver stiffness and the patient-specific liver structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilizing FEM to simulate the interaction between magnetic and mechanical forces has been successfully demonstrated in previous work [21] and been successfully applied to CMs [8]. In addition, the use of ANNs as surrogates of FEMs has also been reported; for example in [26] and [27] convolutional neural networks are used to fully recreate FE simulations of a liver and an arterial wall respectively. These works exhibit results evidencing the effectiveness of deep learning in this particular sphere of research.…”
Section: Design Approachmentioning
confidence: 99%